Ron Ryder banding bird - Lindquist, Mark, photographer (Colorado State University. Libraries, 1999)
Ron Ryder banding bird on SGS, probably a young raptor (added to db 7/21/2000).
Keywords: SGS; bird banding; Ryder, Ron